THE INFLUENCE OF INTERNAL AUDIT, EFFECTIVENESS OF CONTROL AND ACCOUNTING INFORMATION SYSTEMS ON FRAUD DETECTION (STUDY AT DOMPU REGIONAL DRINKING WATER COMPANY) - M. Ikhwan Mansyuri; Samsudin Samsudin; Miskan Arsyad; Yulianti Yulianti (Bajang Institute, 2023)
This study aims to determine internal audit, internal control effectiveness, and accounting information systems on fraud detection at the Dompu Regional Drinking Water Company (PDAM). Sampling using purposive sampling method and analysis tools using multiple linear regression method with a total of 55 employees as respondents. The data collection method used is a questionnaire. The results of this study indicate that internal audit, internal control effectiveness influences fraud detection. Meanwhile, the accounting information system has no effect on fraud detection. The Adjusted R Square value for the coefficient of determination is 0.366 or 36.6% of the level of fraud detection. The remaining 63.4% is influenced by other factors that are not included in this research method.